Rekayasa Model Tiga Faktor Fama dan French Dimoderasi Creative Accounting pada Indeks Kompas 100 - Yuki Dwi Darma; Pujiharta Pujiharta; Emmelia Tan (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to reconstruct the Fama and French Three-Factor Model by incorporating creative accounting as a moderating variable in explaining stock returns in the Indonesian capital market. The capital market plays a crucial role as a mechanism for allocating long-term funds; however, stock return determination is still influenced by market risk, firm fundamental characteristics, the quality of accounting information, and investor behavior. The CAPM model, which emphasizes market beta, is considered insufficient to fully explain variations in stock returns. The Fama and French Three-Factor Model then introduces market risk premium, size, and book-to-market factors as key determinants, yet its effectiveness is not always consistent in emerging markets such as Indonesia. Market conditions characterized by semi-strong form efficiency, information asymmetry, economic volatility, and creative accounting practices may reduce the relevance of financial reporting and influence investment decisions. Therefore, adding creative accounting as a moderating variable is expected to improve the model’s quality, strengthen investor confidence in financial information, and provide a more accurate basis for investment decision-making.